Race, transformation and education as contradictions in a neoliberal South Africa - Isha Dilraj (The Thinker)
In navigating the complexities of race and inequality in South African society, shadowed by colonialism and apartheid, the term transformation has gained traction as the mantra for growth, retribution, education reform, and economic and societal prosperity. However, the capitalistic and neoliberal environment within which the country operates has resulted in transformation initiatives becoming an obsolete contradiction. The education arena, in particular, exemplifies this contradiction and the plethora of inequalities still prevalent in society today. Race has been, and still is, at the forefront of understanding societal inequalities and socio-economic challenges, even though it doesn’t operate in isolation, and relies on the chaotic politics of intersectionality to reveal how power operates in ways which occlude and disguise different kinds of inequalities. In this article, I focus on race as a construct and its deep-rooted significance in South African society, by dissecting conceptualisations of race as a signifier and symbolic, as a structure of division and marker of exclusion, and as a construct of power. Presenting these conceptualisations of race sets the foundation for understanding why transformation initiatives became focal and imperative in charting a new, democratic course in the country. However, these initiatives have become blatant contradictions, as exemplified in the Covid-19 moment in relation to the education sector and the return of students to schools, highlighting deep-rooted inequalities. In acknowledging the severe plight of South African society, handicapped by a superfluity of disparities and discrimination, an offer of hope to reimagine society is deliberated as a way forward, by analysing concepts of antiracism, decoloniality, and a turn to re-defining transformation initiatives to free society from the captivity of neoliberal mentality.